2006
DOI: 10.1111/j.1471-4159.2006.04397.x
|View full text |Cite
|
Sign up to set email alerts
|

Propionate increases neuronal histone acetylation, but is metabolized oxidatively by glia. Relevance for propionic acidemia

Abstract: In propionic acidemia, propionate acts as a metabolic toxin in liver cells by accumulating in mitochondria as propionyl-CoA and its derivative, methylcitrate, two tricarboxylic acid cycle inhibitors. Little is known about the cerebral metabolism of propionate, although clinical effects of propionic acidemia are largely neurological. We found that propionate was metabolized oxidatively by glia: [3-14 C]propionate injected into mouse striatum or cortex, gave a specific activity of glutamine that was 5-6 times th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 48 publications
2
46
0
1
Order By: Relevance
“…34,35 For example, the injection of 14 C-labeled propionate to the striatum or cortex of mice resulted in five to six times higher labeling of glutamine relative glutamate. 34 Ebert et al 35 reported that the metabolism of 13 C-octanoate in the brain occurs predominantly in the glial compartment based on the greater enrichment of glutamine over glutamate. Together, these findings suggest that the potential anticonvulsant effect of triheptanoin may begin or take place primarily in glia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…34,35 For example, the injection of 14 C-labeled propionate to the striatum or cortex of mice resulted in five to six times higher labeling of glutamine relative glutamate. 34 Ebert et al 35 reported that the metabolism of 13 C-octanoate in the brain occurs predominantly in the glial compartment based on the greater enrichment of glutamine over glutamate. Together, these findings suggest that the potential anticonvulsant effect of triheptanoin may begin or take place primarily in glia.…”
Section: Discussionmentioning
confidence: 99%
“…12,13,34 It has been hypothesized that, in certain forms of epilepsy, TCA cycle intermediates may be deficient in the context of neuronal hyperexcitability. 11 Willis et al 11 reported that dietary triheptanoin restored malate levels in the brain of pilocarpineinduced status epilepticus mice, who also experienced an increase G1D, glucose transporter type I deficiency; GABA, g-aminobutyric acid; TCA, tricarboxylic acid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Odd-chain fatty acids, in particular propionate, take a different enzymatic pathway leading to succinyl-CoA. Two of the propionate metabolites (propionylCoA and 2-methylcitrate) having inhibitory effects on the Krebs cycle (Nguyen et al, 2007), propionate is largely used as a precursor of gluconeogenesis. Considering the limited absorption of glucose, and the similar whole body glucose requirements in ruminants and monogastrics (Lindsay, 1981), ruminants rely on hepatic gluconeogenesis for 85% of their whole body glucose turnover (Ortigues-Marty et al, 2003a).…”
Section: Metabolism Of Vfa and Glucose By Portal-drained Visceramentioning
confidence: 99%
“…In addition to passive accumulation in CNS cells, there is also evidence that PPA and other short chain fatty acids are specifically taken up by monocarboxylate receptors in cerebrovascular endothelium, neurons and glia [90][91][92] . PPA is metabolized by glial cells which involves the propionyl CoA carboxlyase enzyme [93] . PPA increases the levels of the cytotoxin propionyl CoA and depletes cytosolic carnitine stores leading to a reduction in fatty acid metabolism by mitochondria which can cause further reductions in intracellular pH [50,51] .…”
Section: Fig 6: Group Means (±Sem) For (A) Glutathione (Gsh) (B) Glmentioning
confidence: 99%